2016
DOI: 10.1080/01932691.2016.1172315
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and physicochemical properties of promising avermectin microemulsion with biodegradable surfactant and oil

Abstract: Green microemulsion suitable for oil-soluble pesticide delivery has been prepared using butyl acetate as oil phase, alkyl polyglycoside (APG) and linear alkylbenzene sulfonate (LAS) as mixed surfactant, and short chain alcohol as cosurfactant. Pseudoternary phase diagrams were constructed to investigate the effects of APG and LAS mixing ratio, the chain length of the cosurfactant on the microemulsion phase behavior. A fully dilutable region run through the phase diagram can be observed and the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…When σ reaches the maximum value (1.25 S m −1 , φ w ≈ 40%), then a phase inversion from reverse swollen micelles (w/o) to direct micelles (o/w) is suggested 23 , 32 . Thereafter, σ values then drop because of dilutional impacts 33 . The structure of the microemulsion from w/o to a discontinuous phase and then o/w using titration is indicated by the derivative of the conductivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When σ reaches the maximum value (1.25 S m −1 , φ w ≈ 40%), then a phase inversion from reverse swollen micelles (w/o) to direct micelles (o/w) is suggested 23 , 32 . Thereafter, σ values then drop because of dilutional impacts 33 . The structure of the microemulsion from w/o to a discontinuous phase and then o/w using titration is indicated by the derivative of the conductivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Once the diluted microemulsion systems reached a new balance again, the droplet size tended to become stable with time. Therefore, a microemulsion possessing macroscopical dilution stability was obtained 7 , 35 .
Figure 3 The variation of droplet size of 5% norcantharidin microemulsion based on time under different dilution times with standard water (342 mg/L).
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, NEs incorporating pesticides settle evenly on the leaves of plants. Some studies have shown that NE improves the solubility of poorly water-soluble pesticides, resulting in the increasing of bioactivity of the pesticides in comparison with conventional pesticides (Leng et al 2014;Wang et al 2017). Using a Quillaja saponin as a natural surfactant Kumari et al (2018) prepared and characterized thymol NE.…”
Section: Nanoemulsions Applicable In Agriculturementioning
confidence: 99%